2006
DOI: 10.1037/0278-7393.32.3.534
|View full text |Cite
|
Sign up to set email alerts
|

Specificity effects in training and transfer of speeded responses.

Abstract: In 3 experiments, participants, on signal, moved a cursor from a central position to 1 of 8 numerically labeled locations on the circumference of a clock face. Movements were controlled by a mouse in 1 of 4 conditions: vertical reversal, horizontal reversal, combined reversals, or normal (i.e., no reversals). Participants were trained in 1, 2, or 3 of these conditions and were tested 1 week later with either the same or a different condition. There were improvements across training and perfect retention across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
69
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 29 publications
13
69
9
Order By: Relevance
“…However, it has been demonstrated that practice on these tests decreases their novelty and with that the underlying Gf-processes (5) so that the predictive value of the tests for other tasks disappears (17). These findings are compatible with a long history of research on cognitive training in psychological and educational science showing that, although performance on trained tasks can increase dramatically, transfer of this learning to other tasks or domains remains shockingly rare (18)(19)(20)(21).…”
supporting
confidence: 73%
“…However, it has been demonstrated that practice on these tests decreases their novelty and with that the underlying Gf-processes (5) so that the predictive value of the tests for other tasks disappears (17). These findings are compatible with a long history of research on cognitive training in psychological and educational science showing that, although performance on trained tasks can increase dramatically, transfer of this learning to other tasks or domains remains shockingly rare (18)(19)(20)(21).…”
supporting
confidence: 73%
“…In contrast to the supporting evidence for positive effects of training variability, evidence also indicates that learning is highly specific to the training conditions (specificity of training); that is, transfer is most effective when the conditions of transfer closely match the conditions of training. Recent studies have addressed the benefits of specificity in both perceptual and motor components of a task (Healy, Wohldmann, Parker, & Bourne, 2005;Healy, Wohldmann, Sutton, & Bourne, 2006). Healy et al (2006) found that contrary to previous findings on the advantage of training variability, individuals show durability and transfer of performance only when the mental procedures developed during training can be reinstated at testing.…”
Section: U N C O R R E C T E D P Rcontrasting
confidence: 41%
“…Recent studies have addressed the benefits of specificity in both perceptual and motor components of a task (Healy, Wohldmann, Parker, & Bourne, 2005;Healy, Wohldmann, Sutton, & Bourne, 2006). Healy et al (2006) found that contrary to previous findings on the advantage of training variability, individuals show durability and transfer of performance only when the mental procedures developed during training can be reinstated at testing. Thus, the current literature is mixed regarding the benefits of training variability.…”
Section: U N C O R R E C T E D P Rcontrasting
confidence: 41%
See 1 more Smart Citation
“…However, the advantages of training variability appear to be limited to certain conditions, and these conditions are not well understood. For example, in a previous study (Healy, Wohldmann, Sutton, & Bourne, 2006), we found no advantage for variability of practice. Specifically, participants learned to perform a speeded aiming task, which involved finding on the display and moving a mouse cursor from a center start position to target digits that appeared along the circumference of a circular stimulus array (see Figure 1).…”
mentioning
confidence: 78%